A CFD study of a direct solar-driven desorption process for carbon capture under transient conditions. (October 2021) - Nelson, Scott; Luu, Minh Tri; Suo, Si; Milani, Dia; Abbas, Ali
Highlights: The typical stripper in the PCC is replaced by an innovative solar stripper (So-St). The internal design complexities of the So-St unit is addressed via CFD modelling. Design improvements using enhanced heat transfer (EHT) methods are proposed. The performance of porous and solid baffles are compared with the bare So-St tube. Porous and solid baffles can offer a So-St field size reduction by 56% to 65%. Abstract: Solvent-based post-combustion carbon capture (PCC) is the most accessible technology to reduce the greenhouse gas (GHG) emissions from coal-fired power plants, however with a substantial energy penalty. This study investigates a novel concept of solar-powered solvent-based PCC, replacing the traditional stripper unit with a solar collector field (SCF) pipe network. This SCF pipe network consists of modular units termed "solar-strippers" (So-St)s that function to desorb the CO2 gas directly within the solar collector tubes. The internal design complexities of the So-St unit are poorly understood and yet to be optimised. Computational fluid dynamics (CFD) is ideal for modelling complex thermo-physical phenomena that appear in the So-St, including boiling flow, heat transfer, reaction kinetics and thermodynamics. This study develops a rigorous CFD model for a single So-St segment; the first of its kind. The model is used to assess possible design improvements using methods of enhanced heat transfer (EHT), in particular the insertion of porous and solid baffles which increase thermal efficiency and boost vapour formation. The porous and solid baffles are estimated to reduce the So-St field size by 56% and 65%, however demanding 2.5 and 6 times more pumping power, respectively. These incremental design enhancements display the utility of CFD in enabling the So-St concept to become a sustainable low-emissions carbon capture & storage (CCS) technology for cleaner energy production.